2004
DOI: 10.1186/1471-2369-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemokines on proliferation and apoptosis of human mesangial cells

Abstract: BackgroundProliferation and apoptosis of mesangial cells (MC) are important mechanisms during nephrogenesis, for the maintenance of glomerular homeostasis as well as in renal disease and glomerular regeneration. Expression of chemokines and chemokine receptors by intrinsic renal cells, e.g. SLC/CCL21 on podocytes and CCR7 on MC is suggested to play a pivotal role during these processes. Therefore the effect of selected chemokines on MC proliferation and apoptosis was studied.MethodsProliferation assays, cell d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 37 publications
2
33
0
1
Order By: Relevance
“…At least in T cells, it has been shown that CCR7 may control adhesion by regulating the activity of different integrins (32,48). CCR7 has also been described to regulate the proliferation in mesangial cells (42), T cells (45, 49), and hemopoietic precursor cells (21). Finally, recently, it has been shown that CCR7 regulates the invasive ability of carcinoma cells (50).…”
Section: Functions Of Ccr7 In Other Cell Types Apart From Dcsmentioning
confidence: 99%
See 1 more Smart Citation
“…At least in T cells, it has been shown that CCR7 may control adhesion by regulating the activity of different integrins (32,48). CCR7 has also been described to regulate the proliferation in mesangial cells (42), T cells (45, 49), and hemopoietic precursor cells (21). Finally, recently, it has been shown that CCR7 regulates the invasive ability of carcinoma cells (50).…”
Section: Functions Of Ccr7 In Other Cell Types Apart From Dcsmentioning
confidence: 99%
“…Concerning the regulation of the cytoarchitecture, it has been shown that stimulation of CCR7 induces filopodia formation in mesangial cells (38) and morphological polarization in T cells (39,40). Stimulation of CCR7 has also been shown to protect mesangial cells and CD8 T cells from CD95-and etoposide-induced apoptosis, respectively (41)(42)(43). Moreover, CCR7 regulates the migratory speed of naive T cells (40) and human squamous cell carcinoma (44).…”
Section: Functions Of Ccr7 In Other Cell Types Apart From Dcsmentioning
confidence: 99%
“…CCR7 expression did not consistently alter any of the in vitro growth features examined, including proliferation in the presence of CCL21. A few non-leukocyte cell types expressing chemokine receptors were reported to have increased proliferation in the presence of the appropriate chemokine; CCR7-positive kidney mesangial cells showed a proliferative response to CCL21 (25,26), whereas CXCR4-positive human pancreatic tumor cells had enhanced proliferation in the presence of CXCL12 (27). Our data show that CCR7-expressing mammary cancer cells behave differently from other CCR7-expressing non-leukocyte cell types.…”
Section: Discussionmentioning
confidence: 41%
“…Гіперекспресія макрофагами ко-лонієстимулюючого фактора у відповідь на променеве пошкодження сприяє їх поширенню у фокусі ураження, при цьому, синтезуючи цитокіни, вони виконують функ-цію клітинних ефекторів хронічного запалення. Висока концентрація цитокінів і профібротичних молекул, серед яких інтерлейкін-8, фактор некрозу пухлин-μ, ендотелін, TGF-β у ділянках інфільтрації зумовлює фіброзоутворен-ня, що є одним з індукторів апоптозу [6]. Так, колаген І і фібронектин, які є компонентами фіброзного матеріалу склеротично змінених ділянок РПК, площа котрих через місяць після НХПТ становить понад 40% площі зрізів пухлини, поряд з окисними модифікаціями компонентів ремодельованого фіброзного матриксу протягом трива-лого часу після завершення курсу НХПТ є потужними індукторами сигнальних шляхів апоптозу [6].…”
Section: мета роботиunclassified